2005
DOI: 10.1124/jpet.105.093047
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Galantamine and Donepezil for Effects on Nerve Growth Factor, Cholinergic Markers, and Memory Performance in Aged Rats

Abstract: This study was designed to determine 1) whether repeated exposures to the acetylcholinesterase inhibitors (AChEIs) galantamine (GAL) or donepezil (DON) resulted in positive effects on nerve growth factor (NGF) and its receptors, cholinergic proteins, and cognitive function in the aged rat, and 2) whether GAL had any advantages over DON given its allosteric potentiating ligand (APL) activity at nicotinic acetylcholine receptors. Behavioral tests (i.e., water maze and light/dark box) were conducted in aged Fishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 40 publications
4
39
0
Order By: Relevance
“…Several studies have reported that donepezil has no effect or impairs performance in healthy rodents, but that it reverses deficits induced pharmacologically or by brain lesions (Rupniak et al, 1997;Poorheidari et al, 1998;Higgins et al, 2002;Bontempi et al, 2003;Takahashi et al, 2005;Yamada et al, 2005). Donepezil also improves performance of aged rats and mice in the Morris water maze (Hernandez et al, 2006), as well as in spontaneous alternation in the T-maze and in a delayed nonmatch to place task in the radial-arm maze (Bontempi et al, 2003). Additionally, there are reports of donepezil reversing memory deficits induced pharmacologically or by lesions in the radial-arm maze (Braida et al, 1996;Cheng et al, 1996;Cheng and Tang, 1998;Ogura et al, 2000).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Several studies have reported that donepezil has no effect or impairs performance in healthy rodents, but that it reverses deficits induced pharmacologically or by brain lesions (Rupniak et al, 1997;Poorheidari et al, 1998;Higgins et al, 2002;Bontempi et al, 2003;Takahashi et al, 2005;Yamada et al, 2005). Donepezil also improves performance of aged rats and mice in the Morris water maze (Hernandez et al, 2006), as well as in spontaneous alternation in the T-maze and in a delayed nonmatch to place task in the radial-arm maze (Bontempi et al, 2003). Additionally, there are reports of donepezil reversing memory deficits induced pharmacologically or by lesions in the radial-arm maze (Braida et al, 1996;Cheng et al, 1996;Cheng and Tang, 1998;Ogura et al, 2000).…”
Section: Discussionmentioning
confidence: 96%
“…Donepezil reversed scopolamineinduced impairments in spontaneous alternation in the Tmaze in young and aged mice as well as in a delayed nonmatch to place task in the radial-arm maze (Bontempi et al, 2003). Repeated administration of donepezil improved the memory performance of aged rats in the Morris water maze (Hernandez et al, 2006) and reversed amyloid b-induced memory impairments in a delayed matching to position paradigm (Yamada et al, 2005). Additionally, this agent reversed learning impairments in the passive avoidance task induced by lesions in the nucleus basalis magnocellularis and scopolamine (Cheng et al, 1996;Ogura et al, 2000), and ethylcholine mustard aziridinium ion (AF64A) (Cheng and Tang, 1998) induced impairments in eight-arm radial maze tasks (Braida et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies in aged rats have found that chronic treatment with donepezil did not affect spatial working memory (Barnes et al 2000), but improved spatial reference memory (Hernandez et al 2006). Similarly, older adults diagnosed with mild cognitive impairment who were treated with galantamine showed improvements in delayed recall, but not measures of attention, working memory, or susceptibility to interference (Grön et al 2006).…”
Section: Cholinergic Function and Spatial Discriminationmentioning
confidence: 94%
“…Galantamine was tested at doses of 0.3, 1.0, and 3.0 mg/kg while donepezil doses were 0.5, 1.0, and 2.0 mg/kg. These doses were based on data obtained in rats in which brain levels of the compounds and the degree of acetylcholinesterase inhibition were compared across a dose and time (Geerts et al, 2005) as well as recent neuropharmacological and behavioral studies in our laboratory (Hernandez et al, 2006).…”
Section: Drugsmentioning
confidence: 99%